El término ‘ergastulum’ en la primera literatura monástica (ss. IV-V) - Torres, Juana María (Antigüedad y Cristianismo, 1990)
The fundamental object of this study is that of demonstrating that from the last haif of the fourth century some of the texts of the monastic literature utilize the term ergastulum as a synonym for the monks cellula. Due to a semantic assimilation which takes into account the concepts of «isolation», «solitude» and «punishment», certain late latin authors used ergastula to designate the private cells of the monks disregarding whether they lived in communities or were anachorètes, giving a metaphoric use to the term. This argumetation departs from other opinions of modern scholars who interpret the ergastula as being special cells of punishment according to the original meaning of the word.